Plan piloto para la transformación y comercialización de abono orgánico derivado de los residuos generados en la zona urbana del municipio de Ubalá Cundinamarca - Aguilera Romero, Brayan Antonio; Solano Sepúlveda, Jessica Paola (Universidad Antonio Nariño, 2022)
The pilot plan for the transformation and commercialization of fertilizer that is derived from organic waste, generated i from the n the urban area of the municipality of Ubalá is presented due to a need preservation of the environment in which it is based on an implementation of a sustainable business model for the production and marketing of fertilizers. Thus, the following document describes an easy series of phases from the startup of a composting pla nt. in the first phase the diagnosis and characterization are disclosed in which those allows us identifying the current situation of waste management. The study of the waste study in which the current market for fertilizers a in the municipality, a market nd fertilizers is analyzed, as well as relating the feasibility of launching the product on the market. In addition, a kind of procedure is presented, the step by step that m transformation of organic waste into fertilizer, where the ust be followed in the controls and monitoring that occur in the process are identified, along with the necessary tools for the development of the operation of the composting plant. A financial stu validate the performa dy is carried out based on operating and investment costs to nce and utility that the project might generate in the following years in order to know how much it will cost the company DYG Engineering and Environment to implement this pr envi oject. And then, a later a legal environmental study in which describes the ronmental impacts at the time of carrying it out.Finally, in this thesis the industrial engineering is implemented and applied through the circular economy concept throughout knowledge to carry out methods, calculations, design, among others Personas de tod o el mundo que estén buscando trabajos sobre el tema de tu investigación podrán encontrarla en bases de datos.